Design and Optimization of a Cylinder Type Linear Magnetic Gear - Yang Qiaoling; Bao Guangqing; Zhang Bei; Liu Meijun (Jixie chuandong, 2015)
On the basis of theoretical analysis of the working mechanism of traditional magnetic field modulation gear,a cylinder type linear magnetic gear is designed,whose transmission ratio is 2. 67. Its air- gap flux density and static thrust characteristics and dynamic thrust characteristics are calculated by using the finite element analysis method. The correctness of the design is validated through the calculate results. Based on the above,the influence of magnetic field modulate ring size on the gear static thrust and the change rule of the influence are analyzed,and a basis for parameter optimization of a linear magnetic gear is provided. At the last,the optimization of relative width of magnetic field modulate ring is to 0. 6 and the thickness to 3 mm,the air gap width of high- speed side to 1. 2 mm.